Association between TSPO-PET measurable microglial activation and plasma CHI3L1 in multiple sclerosis - Ahola, Venla (My University, 2024)
BACKGROUND Multiple sclerosis (MS) is the most common disabling central nervous system (CNS) disease affecting young adults, especially women. Neurologic symptoms result from inflammatory lesions in brain, spinal cord and optic nerve caused by immune cell infiltration from periphery into brain promoting inflammation, demyelination, gliosis, and neuroaxonal degeneration. Diffuse inflammation across brain, caused by activation of CNS-resident cells, microglia and astrocytes, contributes to disease progression throughout the disease course. Several effective treatments for relapsing-remitting MS (RRMS) are currently available but only few for progressive MS (PMS). Clinical course varies considerably between patients; hence, there is an urgent need for biomarkers. Chitinase-3 like-protein-1 (CHI3L1) is one potential biomarker. In the brain, CHI3L1 participates in neuroinflammatory processes and is produced by activated astrocytes and microglia. Microglial activation can be detected in vivo using TSPO-PET. MATERIALS AND METHODS Study cohort consisted of 54 MS patients (25 progressive MS [PMS] and 29 relapsing-remitting MS [RRMS]) and 17 healthy controls (HCs). TSPO-PET imaging using [11C]PK11195-ligand and blood sampling were conducted concurrently. CHI3L1 was measured with commercial ELISA-kit from plasma samples. Additionally, clinical evaluation and magnetic resonance imaging (MRI) were performed. RESULTS Plasma CHI3L1 concentration was increased in MS compared to HCs (median 20.9 ng/ml vs. 16.8 ng/ml; p = 0.0497). CHI3L1 concentration was significantly higher in PMS than in HC (23.5 ng/ml vs. 16.8 ng/ml; p = 0.0055). There was a correlation between specific [11C]PK11195-binding, presented as brain distribution volume ratio (DVR), and CHI3L1 plasma concentration in MS patients (Spearman correlation, r = 0.31, p = 0.049) and in PMS patients (r = 0.56, p = 0.0499). Additionally, CHI3L1 concentration correlated with brain volume in both MS (r = -0.38, p = 0.0051) and PMS (r = -0.49, p = 0.013), but not with MS related clinical variables such as disease duration and the Expanded Disability Status Scale (EDSS). Notably, CHI3L1 concentration correlated strongly with age (r = 0.39, p = 0.0035) in MS cohort but not in PMS (p = 0.13) cohort. CONCLUSIONS Correlation between CHI3L1 and microglial activation in brain suggests that CHI3L1 is a promising biomarker for MS progression related pathology and smouldering inflammation.
Keywords: CHI3L1, Microglia, Multiple Sclerosis, TSPO-PET